Eicosanoids in the Innate Immune Response: TLR and Non-TLR Routes. (17th May 2010) - Alvarez, Yolanda; Valera, Isela; Municio, Cristina; Hugo, Etzel; Padrón, Francisco; Blanco, Lydia; Rodríguez, Mario; Fernández, Nieves; Crespo, Mariano Sánchez
Abstract : The variable array of pattern receptor expression in different cells of the innate immune system explains the induction of distinct patterns of arachidonic acid (AA) metabolism. Peptidoglycan and mannan were strong stimuli in neutrophils, whereas the fungal extract zymosan was the most potent stimulus in monocyte-derived dendritic cells since it induced the production ofPGE 2, PGD 2, and several cytokines including a robust IL-10 response. Zymosan activatedκ B-binding activity, but inhibition of NF-κ B was associated with enhanced IL-10 production. In contrast, treatments acting on CREB (CRE binding protein), includingPGE 2, showed a direct correlation between CREB activation and IL-10 production. Therefore, in dendritic cells zymosan induces il10 transcription by a CRE-dependent mechanism that involves autocrine secretion ofPGE 2, thus unraveling a functional cooperation between eicosanoid production and cytokine production.